Hubungan dukungan sosial dan self-esteem terhadap resiliensi pada ibu menyusui: A literature review - Yuliani Tampubolon; Nur Alam Fajar; Anita Rahmiwati (Holistik Jurnal Kesehatan, 2026)
Background: Breastfeeding mothers often face various psychological challenges that can affect their ability to adapt to stress during breastfeeding. Social support and self-esteem are considered protective factors that play an important role in fostering resilience in breastfeeding mothers. However, studies integrating these two factors are scattered and not comprehensively structured. Purpose: To examine and analyze the relationship between social support and self-esteem on resilience in breastfeeding mothers. Method: This literature review examined national and international journal articles published between 2018 and 2025. Relevant articles were obtained through scientific databases including Google Scholar, PubMed, BMC Psychology, International Breastfeeding Journal, and Reproductive Health. The keywords used were social support, self-esteem, resilience, and breastfeeding mothers, and were then analyzed critically and thematically based on the research variables. Results: Social support and self-esteem are significantly associated with resilience in breastfeeding mothers. Social support plays a role in increasing feelings of security and emotional support, while self-esteem contributes to strengthening mothers' self-confidence and coping skills in dealing with stress during breastfeeding. The interaction between internal and external factors shapes maternal resilience dynamically and contextually. Conclusion: Social support and self-esteem are important components in building resilience in breastfeeding mothers. Resilience is not formed in isolation, but rather through the interaction of individual psychological resources and social environmental support. Suggestion: The development of contextual and sustainable interventions involving families, healthcare professionals, and peer communities is needed to strengthen the self-esteem and resilience of breastfeeding mothers.   Keywords: Breastfeeding Mothers; Resilience; Self-esteem; Social Support.   Pendahuluan: Ibu menyusui sering menghadapi berbagai tantangan psikologis yang dapat memengaruhi kemampuan mereka dalam beradaptasi terhadap stres selama masa menyusui. Dukungan sosial dan self-esteem dipandang sebagai faktor protektif yang berperan penting dalam membentuk resiliensi ibu menyusui. Namun, kajian yang mengintegrasikan kedua faktor tersebut masih tersebar dan belum terstruktur secara komprehensif. Tujuan: Untuk menelaah dan menganalisis hubungan antara dukungan sosial dan self-esteem terhadap resiliensi pada ibu menyusui. Metode: Penelitian tinjauan literatur terhadap artikel jurnal nasional dan internasional yang diterbitkan pada rentang tahun 2018–2025. Artikel yang relevan diperoleh melalui basis data ilmiah antara lain Google Scholar, PubMed, BMC Psychology, International Breastfeeding Journal, dan Reproductive Health. Kata kunci yang digunakan yaitu dukungan sosial, self-esteem, resiliensi, dan ibu menyusui, kemudian dianalisis secara kritis dan tematik berdasarkan variabel penelitian. Hasil: Dukungan sosial dan self-esteem memiliki hubungan yang signifikan dengan resiliensi ibu menyusui. Dukungan sosial berperan dalam meningkatkan rasa aman dan dukungan emosional, sedangkan self-esteem berkontribusi dalam memperkuat kepercayaan diri serta kemampuan koping ibu dalam menghadapi tekanan selama masa menyusui. Interaksi antara faktor internal dan eksternal membentuk resiliensi ibu secara dinamis dan kontekstual. Simpulan: Dukungan sosial dan self-esteem merupakan komponen penting dalam membangun resiliensi ibu menyusui. Resiliensi tidak terbentuk secara tunggal, melainkan melalui interaksi antara sumber daya psikologis individu dan dukungan lingkungan sosial. Saran: Diperlukan pengembangan intervensi yang kontekstual dan berkelanjutan dengan melibatkan keluarga, tenaga kesehatan, dan komunitas sebaya guna memperkuat self-esteem dan resiliensi ibu menyusui.   Kata Kunci: Dukungan Sosial; Ibu Menyusui; Resiliensi; Self-esteem.